Penggunaan Pelacak DNA untuk Deteksi Papaya ringspot virus dengan Metode Hibridisasi Asam Nukleat - Irsan Nuhantoro; Sri Hendrastuti Hidayat; Kikin Hamzah Mutaqin (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Use of DNA Probe for Detection of Papaya ringspot virus Using Nucleic Acid Hybridization MethodPapaya ringspot caused by Papaya ringspot virus (PRSV) is one of the most destructive diseases of papaya. The disease had not been found in Indonesia, until disease outbreak in Nangroe Aceh Darussalam was reported in 2012. Since then, the disease spread rapidly in most papaya growing areas in Sumatera, Java and Bali. Papaya ringspot virus (PRSV) is generally detected using serological or polymerase chain reaction methods. Improvement in detection method is necessary to facilitate a more reliable tool for controlling the spread of PRSV. The aim of the research was to construct DNA probe for development of detection method based on nucleic acid hybridization. Molecular characterization based on HCPro gene sequence indicated high homology (97.88 to 99.05%) among PRSV isolates from Boyolali (Central Java), Medan (North Sumatera), Sleman (Yogyakarta) and Tabanan (Bali). Two DNA clones of HCPro gene were selected for probe construction and the probes were then labeled using PCR DIG-dioxigenin. Optimization of nucleic acid dot blot hybridization method to achieve strongest positive reaction was developed, i.e. using stringency washes at 1×SSC, 0.1% SDS, incubation at 60 oC for 15’. The DNA probe for PRSV has a high specificity and sensitifity; it could detect PRSV at the lowest concentration of nucleic acid (0.062 µg µL-1).